Surds: Examples - Simplify The Following
Surds: Examples - Simplify The Following
Surds: Examples - Simplify The Following
Surds are numbers that are left in root form ( √) to express its exact value. That is,
it cannot be reduced to a rational number.
If a positive whole number is not a perfect square, then its square root is called a
surd.
Surds have an infinite number of non-recurring decimals.
Surds are irrational numbers.
1 1 1
√𝑎 × 𝑏 = √𝑎 × √𝑏, this is equivalent to (𝑎 × 𝑏)2 = 𝑎2 𝑏2
1 1
𝑎 √𝑎 𝑎 2 𝑎2
√𝑏 = , this is equivalent to ( ) = 1
√𝑏 𝑏
𝑏2
Please note √𝑎 + √𝑏 ≠ √𝑎 + 𝑏
√18 = √9 × 2 = √9 × √2 = 3√2
𝑎 𝑎 √𝑏 𝑎√𝑏 𝑎√𝑏
= × = 2 =
√𝑏 √𝑏 √𝑏 (√𝑏) 𝑏
Example: We can use the expansion of the difference of two squares to rationalize
more complicated expressions involving surds.
Difference of Two Squares: 𝑋 2 − 𝑌 2 = (𝑋 − 𝑌)(𝑋 + 𝑌)
3
2+√2
3 2 − √2
= ×
2 + √2 2 − √2
3(2 − √2)
= 2
(2)2 − (√2)
(3 × 2) − (3 × √2)
= 2
(2)2 − (√2)
6 − 3√2
=
4−2
6 − 3√2
=
2
3
2−√2
3 2 + √2
= ×
2 − √2 2 + √2
3(2 + √2)
= 2
(2)2 − (√2)
1
1+√2
1 1 − √2
= ×
1 + √2 1 − √2
1 − √2
= 2
(1)2 − (√2)
1 − √2
=
−1
= −1 + √2
= √2 − 1.
1
√7+√2
1 √7 − √2
= ×
√7 + √2 √7 − √2
√7 − √2
= 2 2
(√7) − (√2)
√7 − √2
=
7−2
√7 − √2
=
5
2
(3 − 2√5)
= (3 − 2√5)(3 − 2√5)
2
= 32 − 3 × 2√5 − 3 × 2√5 + (2√5)
2
= 9 − 6(2√5) + 22 (√5)
= 9 − 12√5 + (4 × 5)
= 9 − 12√5 + 20
= 29 − 12√5